Assessment of Nurses’ Knowledge and Practice for Prevention of Infection in Burn Patients at Karachi, Pakistan - Khan, Khairunnisa; Noor, Mishal; Hussain, Iqra; Sheikh, Kulsoom; Arshad, Kanwal; Rasheed, Benazeer; Mehndrani, Sri Kant; Bano, Nazneen; Lakhani, Nazish; Pardhan, Shahla (Biological and Clinical Sciences Research Journal, 2025)
Burns “damage the skin or any organic tissue that is mainly caused by fire, electricity, radioactive, radiations, and chemical substances”. Every year, approximately 200,000 people around the world die of burn injuries. Though, nurses are crucial for ensuring safety and leads to healthier recoveries for patients. Objective: The Objective of this study is to assess nurses’ knowledge and evaluate their practice for the prevention of infection among burn patients. Method: An analytical cross-sectional study was conducted amongst 100 nurses, and an adopted questionnaire was used from July 2024 to January 2025, in burn units of 03 selected public and private hospitals of Karachi. Results: The majority of respondents were aged between 31-39 years (37.5%). Females constituted the majority of respondents (58.3%), who had completed mainly their Diploma (55.0%) and had 1-5 years of work experience (41.3%), Knowledge of infection control measures (82.5%), and (57.5%) consistently followed PPE protocols during emergencies. As a consequence, they have unsatisfactory information regarding the prevention of infection in burn patients. Whereas, chi square test was used in the inferential statistics where the diploma holder were unaware regarding the knowledge as compared to BSN as P value =0.025, while related to gender; Females were not adhering to the practice of hand washing as compared to male as (P value= 0.05), significantly contractual nurses were unaware about decontaminating hydrotherapy rooms 25(75.8%) as compared to permanent nurses 25(53.2%)as (P value= 0.001), and as well as contractual nurses were 17(51.5%) reported not performing the required hand hygiene, compared to permanent employees 11(23.4%) (P value=0.009) significantly. Conclusion: Based on the findings, it is concluded that nurses working in burn units have limited knowledge and practices regarding prevention of infections among burn patients. Therefore, hospitals are required to organize adequate training, hands-on practice, and frequent exposure in burns ward to develop unit-specific clinical infection control guidelines and protocols.